Changes of the Employment Structure in the Tourism Sector and Further Tendency of E-Tourism in Hungary - Hajdú, Noémi; Lipták, Katalin (Turizam, 2017)
The study will analyzes and compare changes of the employment in two different years (2008 and 2013) in Hungary NUTS 2 level regions. The labor market of these NUTS 2 level regions had an influence of the economic crisis lately and the most of states have not yet recovered from the deep recession. Even though the employment policies were introduced significantly, the labor market was affected negatively by the crisis. The calculation of difference analysis is solved by using shift-share analysis on regional levels of Hungary. A shift-share analysis determines the relationship between economic growth indicators and other national or regional factors. The analysis helps to identify regional sectors which have competitive advantages. A shift-share analysis takes account of the employment changes over time among industries of a regional economy. Then it classifies the employment changes into various components. The relationship between the tourism employment and the other sectoral employment will be illustrated.We analyzed the problem which is so called “20-80 societies” and occurred by the impact automation processes.